Methodical errors in meteorological measurements during correlation processing of signals from radio acoustic sensing systems. Communication 2 - Карташов, В.М.; Бабкин, С.И.; Толстых, Е.Г. (Radiotekhnika, 2017)
Methodological errors estimation of the air humidity measurement arising from the a priori uncertainty of other meteorological parameters altitude distribution is made. Their influence in recording vertical profiles of the measured meteorological value is estimated using correlative processing of the received signals of radio acoustic sensing systems. It is shown that for an arbitrary choice of a pair of sounding audio frequencies, the methodical error of measuring the relative humidity can reach 100% even with a thermal turbulence. The influence of a wind and sounding wave refractive effects on the formation of the methodical measurement error can be reduced by rational selecting technical parameters of the sounding system’s antenna arrangement.